A new redfin species, Pseudobarbus skeltoni (Cyprinidae, Teleostei), from the Cape Floristic Region, South Africa - Chakona, Albert; Swartz, Ernst R. (Zootaxa, 2013)
A new cyprinid species, Pseudobarbus skeltoni sp. nov, is described from material recently collected in the upper Riviersonderend River (a major tributary of the Breede River system) and the Krom River (a tributary of the Molenaars River in the upper Breede River) in the Cape Floristic Region of South Africa. The new species is readily distinguished from congeners, except P. burgi and P. burchelli, by having two pairs of prominent oral barbels. Pseudobarbus skeltoni can be distinguished from P. burgi and P. burchelli by the following combination of characters: distinctive terminal (vs. subterminal) mouth in adults; mouth inferior in sub-adults and young adults of P. skeltoni but lower lips are unretracted (vs. retracted) and lack a distinct cartilaginous plate; snout prominent; more slender head (head depth 64.2% of HL, vs. 70.1% of HL in P. burchelli and 74.1% of HL in P. burgi); and a longer head relative to standard length (30.5 % vs. 26.8% in P. burchelli and 25.8% in P. burgi). The new species attains the largest size of any Pseudobarbus. The restricted distribution and the small remaining population sizes of P. skeltoni indicate that this species is highly threatened and requires immediate conservation attention.